Competency of Faculty Members in Online Teaching of Agricultural Undergraduates during COVID-19 Pandemic: A study in North-East India (Indian Journal of Extension Education, 2021)
Quality education is crucial for growth and development of a nation. Teaching learning process worldwide which was disrupted by COVID-19 pandemic has found consolation through online remote teaching. Competency of teachers plays an important role in the success of online teaching. The study was conducted in North Eastern region (NER) of India to assess the faculty members’ competency in online teaching of agricultural undergraduates. For the study, all the teachers of institutes in NER imparting undergraduate level degree course in Agriculture were selected. Online questionnaire was sent to all the teachers of which 75 responses were received, which formed the respondents of the study. Five online teaching competency dimensions were considered for the study. The respondents had highest mean competency score in Teaching Ethics and lowest in Content Facilitation. Online teaching competency had significant and positive correlation with online teaching experience; attitude towards online teaching; and organisational facilities & support. The study recommends providing organizational facilities and support in the form of adequate infrastructure and conducting trainings on awareness and usage of e-teaching resources and tools to improve the online teaching competency of the teachers.